PENGEMBANGAN MEDIA MONERGI (MONOPOLI ENERGI) UNTUK MENUMBUHKAN KEMAMPUAN PEMAHAMAN KONSEP IPA SISWA SD - Ulfaeni, Siti (Universitas Muhammadiyah Surakarta, 2017)
This research applied media development monergi (monopoli energi) which helps the students understanding of science and how implementation media monergi (monopoli energi) be able to increase the students understanding in science.This subject of the research were students 3B grade, academic year 2016/2017 with total students 38.Â The data from this research calculated by pretest and also posttest, questionnaire responds the students about the media. Questionnaire from expert validations media and also material. The scoring expert validations media and also material trough 2 steps, found from presentation from validation 1 and 2 that will be found the average presentation 77% with the criteria